Identifikasi Miskonsepsi Siswa Bergaya Kognitif Impulsif Dan Reflektif dalam Menyelesaikan Soal Matematika Kelas XII MIPA di SMAN 3 Kota Jambi - Sinaga, Martha Ervina; Harman, Harman; Yarmayani, Ayu (PHI: Jurnal Pendidikan Matematika, 2022)
Misconceptions are misunderstandings of concepts that students have that conflict with concepts that have been agreed upon by experts, misunderstandings of this concept can occur due to the learning methods used in this Covid-19 era, namely limited online and face-to-face methods. The limited interaction between teachers and students can lead to misconceptions, where the concepts given by the teacher and those received by students can have different meanings. Differences in the cognitive style of students in working on math problems can also be the cause of students experiencing misconceptions. The purpose of this study was to identify the misconceptions that occur in students who are cognitively impulsive and reflective in solving math problems. The type of research used is qualitative research, which uses a descriptive research methodology. The research subjects were students of class XII MIPA 2 SMAN 3 Jambi City. The data collection methods used in this study were tests and interviews, where the test consisted of MFFT (Matching Familiar Figures Test) to classify students' cognitive styles, after which two people were selected from impulsive and reflective cognitive styles. Furthermore, the selected students were given a test about the distribution of material and the binomial probability function, as well as interviews with students. The results showed that impulsive students were identified as having misconceptions of translation, systematic, concepts and signs. Meanwhile, reflective students were identified as having misconceptions of strategies, concepts, signs and systematics. The cause of the misconceptions experienced by students is the lack of preconceptions that students have so that in understanding new concepts students become wrong and also students are still in a hurry to solve problems. The results of this study also show the types of misconceptions that occur in all subjects, both impulsive and reflective, namely conceptual misconceptions.